A LITERATURE STUDY OF FINANCIAL STATEMENT FRAUD DETECTION - Yuliana, Yessy; Hartono, Agusti; Fernando, Alvin; Meiden, Carmel; Apriwenni, Prima; Nurlela, Nurlela; Dema, Yosef (International Journal of Social Science, 2022)
This research attempts to give an overview of the focus and methods utilized to identify financial statements in Indonesia. This study employed the systematic literature review (SLR) methodology to analyze how the literature on financial reporting develops. Keywords like "financial statement fraud," "fraud triangle," "fraud diamond," and "fraud pentagon" are used in this study to find related research. 79 studies were found between 2017 and 2020, and 39 of them were used in this research. The findings of this literature review can help researchers develop more in-depth fraud research in the future. Several variables can be utilized as a reference for future research on fake financial statements, such as broadening the scope of the investigation, expanding the object, and involving people who can help with the investigation.